A Comparative Study Of The Psycho-Social Profile Of Drug Using And. Non-Drug Using. School Children. - Choo, Piang Fong; Ismail, Maznah; Navaratnam, V.; Hoo, See Kong (Pusat Penyelidikan Dadah Kebangsaan, Universiti Sains Malaysia, 1986)

(untitled)
Studies conducted by the National Drug Research Centre during 1976/1977 have shown that 11.5% of 16,166 school children surveyed have had some experience with the non-medical use of drugs and that a trend towards multiple drug use was becoming evident. In addition to this, epidemiological studies conducted by the Centre also showed that 30% of the addicts started using drugs before reaching the age of 19 (Navaratnam, 1981). In the same study, based on the data collected from the upper secondary schools in Penang State, it was found that 13.7% of the upper secondary school students aged 16 to 18 years were drug users.